Purification and characterization of a Cys-Gly hydrolase from the gastropod mollusk, Patella caerulea. (1st November 2016) - Cappiello, Mario; Spinelli, Matteo; Mormino, Maurizio; Renzone, Giovanni; Scaloni, Andrea; Moschini, Roberta; Balestri, Francesco; Mura, Umberto; Del-Corso, Antonella
Abstract: A magnesium-dependent cysteinyl-glycine hydrolyzing enzyme from the gastropod mollusk Patella caerulea was purified to electrophoretic homogeneity through a simple and rapid purification protocol. The molecular masses of the native protein and the subunit suggest that the enzyme has a homohexameric structure. Structural data in combination with kinetic parameters determined with Cys-Gly and compared with Leu-Gly as a substrate, indicate that the purified enzyme is a member of the peptidase family M17. The finding that an enzyme of the peptidase family M17 is responsible also in mollusks for the breakdown of Cys-Gly confirms the important role of this peptidase family in the glutathione metabolism.